Charles Goodwin Ridgely journal - Ridgely, Charles Goodwin, 1784-1848.
Two volume journal kept by Ridgely while on board the USS Constellation (Frigate) in the U.S. Navy Pacific Squadron and the USS Erie (Sloop of war) and the USS Independence (Ship of the line) in the U.S. Navy Mediterranean Squadron.
Naval officer.
Collection material is in English.
Keywords: United States. -- Navy; United States. -- Navy -- Foreign service -- Mediterranean Region; United States. -- Navy -- Foreign service -- Pacific Area; United States. -- Navy. -- Mediterranean Squadron; United States. -- Navy. -- Pacific Squadron; Erie (Sloop of war); Independence (Ship : 1814-1913); Constellation (Frigate); Naval officers